The Role of Communication Satisfaction in Improving the Effectiveness of Communication and Organizational Performance of Family Planning Extension Centers - Adi, Fajar; Muljono, Pudji; Martua Damanik, M. Rizal; M. Anwas, E. Oos (JALOW | Journal of Agribusiness and Local Wisdom, 2024)
The Family Planning Program (FP) is one of the Government's efforts to improve community welfare, through child birth regulation. This study aims to analyze the effect of communication satisfaction on communication effectiveness and organizational performance of FP extension centers. This study is descriptive explanatory using statistical analysis and survey design. The Slovin formula is used to determine the number of samples, with a total sample of 430 samples and the sampling technique used is stratified random sampling. There is a positive and significant influence of communication satisfaction on the effectiveness of organizational communication in the FP extension center and the organizational performance of the FP extension center. Central and local governments, as well as other related parties in order to pay attention to the communication satisfaction in improving the effectiveness of communication and organizational performance of FP extension centers